1998
DOI: 10.1136/jnnp.64.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Possible risk factors for primary adult onset dystonia: a case-control investigation by the Italian Movement Disorders Study Group

Abstract: Objectives-Little is known about the aetiology of idiopathic adult onset dystonia. The Italian Movement Disorders Study Group promoted a case-control study on some hypothetical risk factors including past medical events, life events, life habits, occupational hazards, and family hystory of dystonia, parkinsonism, and tremor. Methods-Cases aVected by idiopathic adult onset dystonia (age at symptom onset >20 years, duration of disease >one year and Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
125
3
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(144 citation statements)
references
References 23 publications
10
125
3
2
Order By: Relevance
“…Such an increased incidence of Parkinson’s disease, however, does not appear to occur in BEB patients [106]. The eye irritation environmental trigger, however, is consistent with the human data [36-39] and the evidence that changes in the basal ganglia plays a role in the predisposing condition is compelling [40, 97-99]. Thus, the Schicatano et al (1997) model [100] suggests an outline for abnormal neural circuit interactions that support BEB.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Such an increased incidence of Parkinson’s disease, however, does not appear to occur in BEB patients [106]. The eye irritation environmental trigger, however, is consistent with the human data [36-39] and the evidence that changes in the basal ganglia plays a role in the predisposing condition is compelling [40, 97-99]. Thus, the Schicatano et al (1997) model [100] suggests an outline for abnormal neural circuit interactions that support BEB.…”
Section: Introductionsupporting
confidence: 69%
“…These characteristics are exaggerations of the normal blink adaptation to the corneal irritation created by dry eye [35]. Thus, it is not surprising that a significant proportion of patients report current or previous experiences of dry eye when first diagnosed with BEB [36-39]. Nevertheless, the vast majority of individuals with dry eye do not go on to develop BEB.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published well designed study found an evidence of ocular disease such as dry eye, blepharitis and keratoconjuctivitis in 50 of 140 patients with BPS 10 . Previous studies have showed non-significant associations between alcohol use, hypertension and minor head trauma (without loss of consciousness) with BPS 13 . On the other hand, head trauma with loss of consciousness 13 and as a protective caffeine intake 14 , have been suggested as a risk factor and as a protective factor, respectively.…”
Section: Demographic and Clinical Featuresmentioning
confidence: 74%
“…Previous studies have showed non-significant associations between alcohol use, hypertension and minor head trauma (without loss of consciousness) with BPS 13 . On the other hand, head trauma with loss of consciousness 13 and as a protective caffeine intake 14 , have been suggested as a risk factor and as a protective factor, respectively. The lack of a control group in our study precluded confirmation of those associations.…”
Section: Demographic and Clinical Featuresmentioning
confidence: 74%
See 1 more Smart Citation